Presence of endoparasites in the Greek buffalo (Bubalus bubalis) from Northern Greece - FOUNTA, A.; PAPADOPOULOS, E.; CHLIOUNAKIS, S.; BAMPIDIS, V. A.; PAPAZAHARIADOU, M. (Journal of the Hellenic Veterinary Medical Society, 2018)
This study was conducted in order to determine the presence of parasitic infections of the Greek buffalo (Bubalus bubalis) in the Prefecture of Serres, Northern Greece. During the period from February to October 2014, faecal samples from 110 buffaloes of the Greek buffalo breed (Bubalus bubalis), from 9 farms located in proximity to Lake Kerkini, in the Prefecture of Serres, Northern Greece, were examined, in order to find reproductive elements of parasites. Out of 110 faecal samples examined, 102 (92.73%) were found infected with reproductive elements (eggs, larvae, cysts and oocysts) of parasites. Specifically, the parasites found were: Eimeria spp. (40%), Entamoeba bovis (16.36%), Paramphistomum cervi (10%), Fasciola hepatica (16.36%), Dicrocoelium dendriticum (28.18%), Moniezia benedeni (27.27%), Toxocara vitulorum (11.82%), Strongylida (gastrointestinal nematodes) (31.82%) and lungworms (28.18%). The present study appears to be the first report of the detection of lungworms in buffaloes, in Greece.